Alleviating effect of intranasal zinc on symptoms of allergic rhinitis - Huadong Xu, PhD; Keming Tong, BS; Naruhito Iwasaki, MD, PhD; Nobutaka Ohgami, PhD; Akira Tazaki, PhD; Takumi Kagawa, MMSc; Yanjun Gao, MMSc; Delgama A.S.M. Nishadhi, MMSc; Akihito Harusato, MD, PhD; Masafumi Sakashita, MD, PhD; Kazuhiro Ogi, MD, PhD; Shigeharu Fujieda, MD, PhD; et al. (Journal of Allergy and Clinical Immunology: Global)
Background: There is no information about the clinical implications and kinetics of zinc (Zn) in the nasal cavity, a center of allergic inflammation, and serum in subjects with allergic rhinitis (AR). Objective: Effects of intranasal Zn on symptoms before and after allergen provocation were investigated in humans and mice with or without AR. Methods: The first clinical follow-up study for Zn levels in nasal epithelial lining fluid (ELF) and serum was conducted in 57 control subjects and 44 patients with Japanese cedar pollinosis (JCP), a representative seasonal AR, from preseason to season. The clinical implications and kinetics of Zn levels in ELF and serum were further investigated in model mice with JCP. Results: This clinical study showed that the Zn level in nasal ELF from patients with JCP was increased after pollen exposure and became significantly higher than that in nasal ELF from controls in the JCP season. Conversely, the serum Zn level in patients was decreased after pollen exposure and became significantly lower than that in the controls in the JCP season. To further investigate the clinical implication of Zn level, model mice that mimicked the kinetics of intranasal and serum Zn levels as well as the symptoms in patients with JCP were established. The mouse interventional study showed that the symptoms of mice with provocative JCP were significantly improved by treatment with the putative human-equivalent dose of Zn. The relative number of mucin-secreting goblet cells, a sign of provocative allergic rhinitis, in the mice was decreased by intranasal treatment with Zn. Conclusion: The study’s behavioral and pathologic results indicate that an increased level of intranasal Zn can alleviate symptoms of AR.